DETERMINATION OF THE MAIN DISPATCHER DOMINANT STUDENTS CONDUCT UNDER VIOLATION OF SEPARATION - Борсук, С. П. (Science-based technologies, 2015)
Main behavior dominants for the air traffic controllers-students are observed in the article in conditions of flight norms violation during the flights. Process of the polling is described for the group of controllers-students along with the way of their main behavior dominant determination. Example of main dominant determination basing on received data is given. Conclusions and recommendations on further researches are proposed.